Ethnic enclaves and immigrant self-employment: A neighborhood analysis of enclave size and quality - Martin Andersson; Johan P. Larsson; Özge Öner (Research Institute of Industrial Economics (IFN), 2017)
We explore the effects of neighborhood-level ethnic enclaves on the propensity of immigrants to use business ownership as a vehicle to transcend from labor market outsiders to insiders. We exploit an exogenously partitioned grid of geocoded 1-by-1 km squares to approximate neighborhoods, and match it with Swedish full-population data from 2011-2012 to study immigrants from the Middle East. We demonstrate a robust tendency for people to leave non-employment for self-employment if many members of the neighborhood ethnic diaspora are business owners, while we observe weak effects emanating from business ownership in other groups. Net of these effects, the overall scale of the enclave, measured by local concentration of co-ethnic peers, negatively influences the propensity to become self-employed. The results are consistent with the argument that it is not the scale, but the quality of local ethnic enclaves that influence labor market outcomes for immigrants.
Keywords: P25; L26; J15; 330; Ethnic enclave; Segregation; Immigrant entrepreneurship; Self-employment; Labor market sorting; Integration